Pendirian Perseroan Terbatas oleh Suami Istri Tanpa Perjanjian Kawin Ditinjau dari Undang-undang No 40 Tahun 2007 tentang Perseroan Terbatas - Elvareta Bayu Samudra (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2018)
One of the most preferred forms of economic enterprise is a Limited Liability Company, because (1) the liability is limited and (2) makes it easy for the owner to divert his company to everyone. In Law No. 40 of 2007 about Limited Liability Companies, explained that: Limited Liability Company was established by 2 (two) or more people. This is the purpose of this paper, there are: the establishment of a Limited Liability Company by husband and wife without a marriage agreement. The conclusion of this paper is that the legal status of a limited liability company requires that the founders consist of at least 2 (two) founders, so that a husband and wife cannot establish a Limited Liability Company. According to The Marriage Law, that a husband and wife are considered to have one interest, namely forming a family - where the husband becomes the head of the family and the wife becomes a housewife, and basically husband and wife are a legal subject.